Robert (Bobby) Lloyd interviewed by James Waites - Lloyd, Robert, 1930-; Waites, James, 1955-2014. (2003)
Robert Lloyd, born in Sydney, N.S.W. (1930) recalls his childhood years in Kirribilli, N.S.W.; his family background, his father's work for the Sydney Morning Herald (SMH); his parents concern for the welfare of the many refugees arriving from Europe from the beginning of the war (WWII). Lloyd discusses in detail a number of the flamboyant artistic types, many from Vienna, that he got to meet and befriend. Lloyd recalls some of the migrants who started up creative activities in Sydney, and his own involvement in Rosemary Benjamin's Children's Theatre. He speaks about leaving school at 16 years of age and taking on a job with interior decorator, Derec Deane; meeting lifelong friend, Peter Hirst. Lloyd talks about going to concerts as a child with the SMH music critic Neville Cardus and, also, a refugee named Hans Forst; his years in London between 1950-53.
Lloyd speaks about his discovery of satirical intimate revue in London and how, on his return to Sydney, meeting up with a group of people with a similar interest. He recalls that this lead to a production called Metropolitan Merry Go Round, involving many of the key figures who went on to form the celebrated Phillip Street revues. Lloyd speaks about his costume making and hire business with Roger Goss; his involvement in the landmark production of Boys In the Band. Lloyd speaks about the opening of the nightclub Capriccios; his new clothing business venture in bridal wear; in later years, finding a new career designing for television, including major advertising campaigns and rock music vidoes. Lloyd speaks about his current work designing stage productions for a number of schools as well as pursuing his passion for fine music, especially Wagner.
Recorded on Dec. 2, 2003; Dec. 29, 2003; Jan. 5, 2004 at Sydney NSW.
Digital master available
Timed summary (29 p.) and uncorrected transcript (typescript, 290 leaves)
Keywords: Lloyd, Robert, -- 1930- -- Interviews; Costume designers -- New South Wales -- Elizabeth Bay -- Interviews; Set designers -- New South Wales -- Elizabeth Bay -- Interviews; Theater -- New South Wales -- Sydney -- 1945- -- Anecdotes; Revues -- New South Wales -- Sydney -- 1965-; Designers